Pathogenesis of HIV-associated depression: contributing factors and underlying mechanisms - Zaongo, Silvere D.; Wu, Wenlin; Chen, Yaokai (Frontiers in Psychiatry, 2025)
Cumulative evidence indicates that compared to HIV negative individuals, people living with HIV (PLWH) have a higher likelihood of developing depression, anxiety, and cognitive disorders. Depression, which is known to be a persistent and overwhelming feeling of sadness accompanied by a loss of interest in usual activities, is one of the most common mental illnesses encountered during HIV infection. Experts believe that several factors such as neuroinflammation, life stressors, lack of sleep, poor nutritional state, opportunistic infections and comorbidities, and HIV medications are contributing factors favoring the development of depression in PLWH. However, the fundamental mechanisms which underlie the involvement of these factors in the emergence of depression in the context of HIV remain poorly explored. Past researches describing the role of one or two of the preceding factors do exist; however, very few articles tackle this important topic while considering the several different putative causative factors comprehensively in the particular context of HIV infection. Herein, we elaborate on the factors currently understood to be responsible for the development of depression, and discuss the particular fundamental mechanisms whereby each factor may result in the outcome of depression. We believe that the understanding of these factors and of their underlying mechanisms is essential for the development of future therapeutic interventions to alleviate the burden of depression commonly seen in PLWH, and therefore facilitate the development of strategies to improve their overall quality of life.